O desencontro entre os sexos: problemáticas amorosas na pós-modernidade - Franceschini, Lilia Guerrero (2014)
Culture traditionally laced by a patriarchal model relied on a phallic jouissance mode, but today the ideals of culture are no longer supported through that typically masculine mode of enjoying. Currently, there is an opening to a new kind of endless pleasure that always seeks for more, as a typically feminine jouissance. Based on that point of view, this paper discusses love concerns contextualized in postmodernity. The mismatch between sexes has been constant cause of complaints at the clinic, and discomfort arising from such dissatisfaction leads to the occurrence of several issues. Is there a new type of man emerging? Does the contemporary woman differ from that of previous decades? What are the possibilities of encounter between sexes? Thus, it will be used a psychoanalytical analysis of sexuality based on Freud and Lacan. Lacanian proposal presents a new way of feminine jouissance, with the existence of formulas to sexualizing the female and male sexual positions and the lack of intercourse. These arguments will base the discusion of the theory of loving partnerships. Among the findings of this study, is the supported hypothesis that loneliness, one of the recurring complaints, backs up on the lack of care that individuals feel to express their own sexual role nowadays